No partiality the idolatry of race and the new humanity - Sharp, Douglas R. 1949- (Downers Grove, IL IVP, 2002)
Includes bibliographical references and indexes.
Keywords: Race relations -- religious aspects -- Christianity; Racism -- religious aspects -- Christianity